Literature Review on the Therapeutic Potential of Bacteriophages Against Resistant Staphylococcus aureus - Hasugian, Ivan Armadi; Zikriyani, Hikmah (Jurnal Biologi Tropis, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) remains a major driver of antimicrobial resistance and necessitates precise non-antibiotic therapeutics. This review comprehensively evaluates evidence on bacteriophage therapy against resistant S. aureus and the molecular and structural barriers that limit efficacy. A structured search of PubMed, Scopus, Google Scholar, ScienceDirect, KAKEN, and ResearchGate identified peer-reviewed studies published up to 2025 using predefined keywords. Articles were screened and synthesized thematically across vitro assays, Ex Vivo burn-wound models, and host-range/biofilm studies, with mechanistic mapping of mecA/PBP2a and O-acetyltransferase A (OatA), and appraisal of dosing strategies (single, repeated, prophylactic). Findings show consistent phage-mediated reductions of S. aureus in vitro; in Ex Vivo human/porcine skin, higher doses and repeated application enhanced suppression, and prophylaxis prevented colonization. Activity against biofilm was strain- and phage-specific; some phages reduced biomass while others paradoxically increased it, and narrow host range plus OatA-linked barriers persisted. In conclusion, bacteriophages are promising but require precise strain matching and micro-environmental consideration. The research highlights the importance of biofilm-aware screening, strategic formulation of phage cocktails or lytic enzymes, optimized dosing regimens for repeated or prophylactic use, and the integration of molecular characterization with synthetic phage engineering to broaden host range and accelerate translation into clinical applications.